Round steel wire for wire thread insert, quenching process and wire thread insert
Through a multi-step quenching process, the microstructure of the round steel wire for wire screws is optimized, which solves the problems of insufficient strength, wear resistance and fatigue resistance in the existing technology, and achieves the comprehensive performance of the material, which is suitable for high-reliability needs for high-end applications.
Patent Information
- Application Number
- CN202411957769.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing round steel wires for wire screws have insufficient comprehensive demand in terms of high strength, wear resistance and fatigue resistance, especially under high stress cycle conditions, which are prone to fatigue failure.
A multi-step quenching process is adopted, including austenitization treatment, primary quenching, redistribution treatment and secondary quenching, to optimize the microstructure and phase structure of the material, and through the synergistic effect of deformation twinning, precipitation phase and dislocation density, the strength, wear resistance and fatigue resistance of the material are improved.
It significantly improves the comprehensive performance of round steel wires for wire screws, and can maintain long-term stability and reliability in high load, strong vibration and dynamic fatigue environments, meeting the performance requirements of high-end applications.
Smart Images

Figure CN119824338A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of steel materials, and in particular to a round steel wire for a wire thread sleeve, a quenching process and a wire thread sleeve. Background Art
[0002] As a high-performance fastener, wire thread inserts have important application value in aerospace, automobile manufacturing, precision machinery and electronic equipment, especially in high-strength connectors and anti-vibration equipment, where their performance is directly related to the reliability and service life of the product. As the core material of wire thread inserts, round steel wire needs to have excellent strength, wear resistance and fatigue resistance to withstand high-intensity mechanical loads and long-term dynamic fatigue in complex environments. In the aerospace field, wire thread inserts are used for high-strength threaded connections of key components, requiring round steel wire to maintain stable performance in extreme temperatures and high vibration environments; in automobile manufacturing, wire thread inserts need to withstand continuous vibration and stress cycles, and the material must have high strength and excellent fatigue resistance to avoid failure; and in precision machinery, its wear resistance is crucial to ensure consistent performance during frequent assembly and disassembly. These application scenarios place extremely high demands on the performance of round steel wire for wire thread inserts, especially the balance optimization between strength, wear resistance and fatigue resistance, which directly affects the overall performance and service life of the product. Meeting these performance requirements can not only significantly improve the reliability of wire thread inserts in high-end applications, but also broaden their application range in extreme environments, promote technological innovation and industry progress of fastener materials, and thus provide strong guarantees for the safety and service life of high-performance machinery and equipment.
[0003] At present, the research and development of round steel wire for wire thread inserts has made certain progress, but there are still obvious deficiencies in meeting the comprehensive requirements of high strength, wear resistance and fatigue resistance. For example, the Chinese patent with publication number CN201982456U discloses a wire thread insert. The patent does not involve any measures for strengthening the microstructure of the material, but in practical applications, it still faces the problem of difficulty in balancing high strength and fatigue resistance, especially under high stress cycle conditions, fatigue failure is prone to occur, which limits its use in high-end equipment. The main reason for these deficiencies is that the existing process has limited control over the microstructure of the material, especially in terms of grain refinement, precipitation phase distribution, and interface property optimization. It is difficult to achieve precise control and it is difficult to simultaneously meet the balance requirements of strength, wear resistance and fatigue resistance. In addition, the existing process has an imperfect control mechanism for residual stress and dislocation density during heat treatment, resulting in a rapid performance degradation of the material under dynamic load. Therefore, developing a round steel wire quenching process for wire thread inserts that can optimize material microstructure and improve comprehensive performance through refined process design has become a key research direction for solving industry technical problems, improving product reliability and expanding the scope of application. Summary of the invention
[0004] The purpose of the present invention is to provide a round steel wire for a wire screw insert, a quenching process and a wire screw insert, so as to solve the problem that the round steel wire for the wire screw insert and the wire screw insert have insufficient strength, wear resistance and fatigue resistance.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The invention discloses a round steel wire for a steel thread sleeve. The chemical components of the round steel wire include, by weight percentage, 0.10-0.22% C, 10.0-13.5% Cr, 0.50-0.60% Si, 0.30-0.35% Mn, 0.15-0.25% Ni, 0.01-0.03% Mo, 0.15-0.20% Cu, 0.005-0.007% Ti, 0.001-0.002% S, 0.025-0.035% P, 0.001-0.002% Al, 0.085-0.090% V, 0.008-0.012% Co, 0.008-0.012% Nb, and the balance is Fe and unavoidable impurities.
[0007] Furthermore, the round steel wire for the steel wire thread insert contains deformation twins, the average width of which is 30 to 65 nm and the average density is 1.1×1012 to 3.5×1012 cm-2;
[0008] The round steel wire for the steel wire thread sleeve contains a short rod-shaped Ni3(Ti, Al) precipitation phase, the average width of the Ni3(Ti, Al) precipitation phase is 5.0-15 nm, and the average length is 50-145 nm.
[0009] Furthermore, the short rod-shaped Ni(Ti,Al) precipitate phase in the round steel wire for the steel wire screw sleeve is dispersed inside the matrix grains, and the spacing between them is 20 to 50 nm;
[0010] The interface between the Ni3(Ti,Al) precipitation phase and the α-Fe in the matrix is a semi-coherent interface; the interface mismatch degree is 1.5% to 3.0%.
[0011] Furthermore, the dislocation density of the round steel wire for the wire thread insert is 5.0×1014 to 1.0×1015 m-2.
[0012] The matrix grains of the round steel wire for the steel wire thread insert are refined to an average grain size of 1.5 to 3.0 μm after redistribution treatment, and the grains show {111} texture characteristics;
[0013] In the round steel wire for the steel wire thread sleeve, the residual compressive stress distribution range at the interface between the Ni(Ti, Al) precipitation phase and the α-Fe matrix is 200-400 MPa.
[0014] Furthermore, the ratio of large-angle grain boundaries to small-angle grain boundaries in the round steel wire for the wire thread insert is (55-70):(30-45).
[0015] The present invention also provides a quenching process for round steel wire for steel wire thread inserts, comprising the following steps:
[0016] S1: pre-treating the hot-rolled round steel wire rod to remove surface impurities;
[0017] S2: austenitizing the round steel wire obtained in step S1 to obtain an austenitic wire rod;
[0018] S3: performing a primary quenching treatment on the austenite wire rod to obtain a martensitic wire rod;
[0019] S4: performing a redistribution treatment and a secondary quenching treatment on the martensitic wire rod in sequence to obtain a finished round steel wire for a wire thread sleeve;
[0020] S5: Drawing the finished round steel wire for wire thread insert to obtain round steel wire for wire thread insert
[0021] Furthermore, the pretreatment process in step S1 is: placing the hot-rolled wire rod of the round steel wire in a pickling tank, adding a 10wt.% dilute nitric acid solution, keeping stirring for 5 to 10 minutes, pickling to remove the surface oxide scale, and after the pickling is completed, rinsing the hot-rolled wire rod with deionized water for 3 times, and placing the rinsed hot-rolled wire rod in a hot air drying oven at 70 to 80°C and drying for 30 to 60 minutes.
[0022] Furthermore, the austenitizing process in step S2 is: placing the pretreated hot-rolled wire rod into a heating furnace, heating it to 1100-1150° C. at a heating rate of 5-10° C. / min, and keeping it warm for 3.0-5.0 min to complete the austenitizing treatment to obtain the austenitic wire rod.
[0023] Furthermore, the process of the primary quenching in step S3 is: placing the austenite wire rod obtained in step S2 into an oil bath at 180-200° C. for quenching, and keeping it in the oil bath for 60-70 seconds to obtain the martensitic wire rod.
[0024] Furthermore, the secondary quenching process of S4 is as follows: placing the martensitic wire rod in a salt bath molten salt at 420-450° C., keeping the temperature for 30-60 minutes to complete the redistribution treatment, and then performing room temperature water quenching to obtain a finished round steel wire for wire thread sleeves.
[0025] Furthermore, the drawing process in step S5 is as follows: a lubricant is applied to the surface of the finished round steel wire for wire thread inserts, and then the round steel wire for wire thread inserts is drawn for 3 to 5 times, with a deformation of 5 to 10% in each drawing process, to finally obtain the round steel wire for wire thread inserts.
[0026] The present invention adopts a multi-step quenching process design mainly to enhance the strength, wear resistance and fatigue resistance of round steel wire for wire thread sleeves, and achieves a significant improvement in material performance through fine control of the quenching process. The core of the quenching process is to optimize the microstructure and phase structure of the material through the mutual coordination of austenitization treatment, primary quenching, redistribution treatment and secondary quenching. In the austenitization treatment stage, by heating the material to 1100-1150°C and uniformly heating at a heating rate of 5-10°C / min, it is ensured that the carbide is fully dissolved and a uniform austenite structure is formed, providing an ideal organizational basis for subsequent quenching transformation, while suppressing grain growth by short-term heat preservation to improve the toughness of the material. In the initial quenching process, by rapidly quenching the austenite wire rod into an oil bath at 180-200°C and keeping it for 60-70 seconds, the austenite is transformed into martensite, significantly improving the hardness and strength of the material, while reducing the formation of thermal stress and internal cracks by precisely controlling the cooling rate. Redistribution treatment and secondary quenching are carried out by placing the martensitic wire rod in a salt bath molten salt at 420-450℃ for 30-60 minutes and then rapidly quenching it with water. On the one hand, the grains are refined to further improve the strength, and on the other hand, dispersed precipitation phases (such as Ni(Ti,Al)) are induced to form in the matrix grains, thereby significantly enhancing the wear resistance and fatigue resistance of the material. In addition, the redistribution treatment at this stage can stabilize the retained austenite, optimize the toughness of the material and improve its dynamic bearing capacity. The entire quenching process is regulated by multi-stage cooling and phase change, which not only achieves the synergistic effect of grain refinement and precipitation strengthening, but also ensures the long-term stability and reliability of the material under high-strength and complex service conditions through the release of residual stress and the improvement of organizational uniformity. Finally, the dislocation density and surface density of the material are further improved through drawing processing, and the wear resistance and fatigue resistance are optimized while meeting the strength requirements, thereby fully meeting the performance requirements of the wire screw sleeve in high-load, strong vibration and dynamic fatigue environments.
[0027] The present invention adopts a multi-component alloy design and a refined quenching process design mainly to enhance the strength, wear resistance and fatigue resistance of round steel wire for wire thread sleeves. By regulating the microstructure of the material, a multi-scale strengthening mechanism is constructed to achieve a comprehensive improvement in performance. The chemical composition design of the round steel wire focuses on the synergistic effect of elements such as C, Cr, Ni, and Ti, wherein the precise control of the C content provides a basis for the precipitation of carbides, while ensuring the stability of austenite during austenitization; the addition of Cr and Ni significantly improves the corrosion resistance and hardenability of the material; Ti and Al further enhance the precipitation strengthening effect of the material by forming a short rod-shaped Ni (Ti, Al) precipitation phase with Ni. Through the optimization of the quenching process, the matrix grains are refined to 1.5-3.0 μm, and the interior of the grains shows a stable {111} texture feature. This texture optimization not only improves the strength and plastic matching of the material, but also significantly improves its fatigue resistance. In addition, the deformation twins formed during the quenching process are distributed in the form of a width of 30 to 65 nm, and their high density characteristics provide an effective barrier to dislocation movement, thereby further strengthening the matrix; and the increase in dislocation density to 5.0×1014~1.0×1015m-2 enhances the overall strength and durability of the material through the dislocation strengthening mechanism. The short rod-shaped Ni(Ti,Al) precipitate phase exists in the form of a dispersed distribution inside the matrix grains, with a spacing controlled at 20 to 50 nm. The semi-coherent interface formed between it and the matrix α-Fe has a mismatch of 1.5% to 3.0%. This interface characteristic not only ensures the bonding strength between the precipitate phase and the matrix, but also effectively hinders dislocation movement, thereby achieving a synergistic improvement in strength and plasticity. At the same time, the distribution of the Ni(Ti,Al) precipitate phase introduces a residual compressive stress of 200 to 400 MPa, which plays an important role in the process of fatigue crack propagation and provides a significant advantage for the material's fatigue resistance. Through redistribution treatment and secondary quenching, the grain boundary characteristics of the material are optimized, and the ratio of large-angle grain boundaries to small-angle grain boundaries is controlled at (55-70): (30-45). This grain boundary distribution not only enhances the coordination of grain boundary sliding, but also improves the stress distribution capacity of the material. In addition, the microstructure of the material forms a multi-scale strengthening mechanism through the above process. The synergistic effect of deformation twins, precipitated phases, residual compressive stress and dislocation density significantly improves the comprehensive performance of the material, thereby meeting the use requirements of wire screw inserts in high-strength fastening, wear-resistant service and fatigue resistance scenarios, and providing a solid guarantee for high-reliability applications under complex working conditions.
[0028] The present invention also discloses a wire screw sleeve, and the preparation method of the wire screw sleeve is as follows:
[0029] A1. Cut the round steel wire into small segments of predetermined length according to the specifications of the wire thread insert, and the tolerance range of the cutting length is controlled to be ±0.05mm.
[0030] A2. The small steel wire segment obtained in step A1 is formed by a spiral forming device; the forming process adopts a cold forming process, the forming temperature is controlled within the range of room temperature to 50°C, the axial pressure during forming is controlled to be 100-300MPa, and the forming speed is controlled to be 20-50mm / s; the pitch tolerance of the formed steel wire thread sleeve is ±0.02mm, and the thread outer diameter tolerance is ±0.05mm.
[0031] A3. The wire screw insert formed in step A2 is subjected to surface treatment, and the surface treatment comprises the following steps: first, the surface of the wire screw insert is cleaned using an ultrasonic cleaning device to remove residues and oil stains; then, an anti-rust lubricant is uniformly coated on the surface of the cleaned wire screw insert, and the thickness of the lubricant coating layer is controlled to be 5 to 13 μm; finally, the coated wire screw insert is placed in a hot air drying oven at 120 to 150°C for curing treatment, and the curing time is 30 to 60 minutes to form a uniform lubricating protective layer.
[0032] The present invention adopts a design combining precision cold forming process with surface treatment, which is mainly used to enhance the dimensional accuracy, mechanical properties and corrosion resistance of the wire screw sleeve, and improves the comprehensive quality and service performance of the wire screw sleeve by optimizing the forming and subsequent processing processes. In the preparation process, the round steel wire is first cut into small segments with precise length according to the specifications of the wire screw sleeve, and the cutting length tolerance is controlled at ±0.05mm to ensure the consistency and precision of the size in the subsequent forming process. Subsequently, the small segments of steel wire are spirally formed by cold forming process at room temperature to 50°C, and the axial pressure and forming speed are precisely controlled to maintain the tolerances of the pitch and the outer diameter of the thread within the range of ±0.02mm and ±0.05mm, respectively, which significantly improves the forming accuracy and dimensional stability of the screw sleeve, and at the same time improves its strength and fatigue resistance through the dislocation strengthening effect introduced by the cold working process. After forming, the wire screw sleeve is cleaned by ultrasonic cleaning to remove surface residues and oil stains, effectively ensuring the uniformity and adhesion of the subsequent coating process; then the anti-rust lubricant is evenly coated, and the coating thickness is controlled at 5-13μm, which not only forms an effective protective barrier on the surface of the screw sleeve, significantly improving its corrosion resistance, but also reduces the friction coefficient during the assembly process to reduce wear; finally, it is cured in a hot air drying oven at 120-150℃ to ensure the uniformity and stability of the lubricant coating. The various steps in the entire preparation process complement each other. The dimensional accuracy of the cutting stage provides a reliable guarantee for the forming process. The optimized process parameters during the cold forming process ensure the mechanical properties and forming quality of the screw sleeve, and the fine surface treatment further enhances the corrosion resistance and service life of the screw sleeve. Through the synergy of the process, the wire screw sleeve has achieved excellent performance in high-precision, high-strength and complex service environments, which significantly meets the needs of aerospace, automobile manufacturing and precision machinery for high-performance fasteners.
[0033] Beneficial Effects
[0034] 1. The present invention significantly outperforms the prior art in enhancing the strength, wear resistance and fatigue resistance of round steel wire for wire thread inserts through the coordinated optimization of a multi-step quenching process. Through precise control of austenitization treatment, primary quenching, redistribution treatment and secondary quenching, the grains are effectively refined, a dispersed Ni (Ti, Al) precipitation phase is generated and the residual austenite is stabilized, thereby achieving a coordinated improvement in strength, toughness and wear resistance. Compared with traditional processes, the present invention significantly improves the microstructural uniformity and residual stress distribution of the material, effectively solves the problems of insufficient strength and fatigue failure in complex service environments, meets the requirements of high-load dynamic working conditions, and promotes the development of the high-performance fastener industry.
[0035] 2. The present invention achieves a significant improvement in the strength, wear resistance and fatigue resistance of round steel wire for wire thread inserts through the coordinated optimization of multi-component alloy design and refined quenching process. The precise ratio of elements such as C, Cr, Ni, Ti, combined with the dispersed distribution of short rod-shaped Ni (Ti, Al) precipitate phase, constructs a multi-scale strengthening mechanism, in which the collaboration of deformation twins, dislocation density and residual compressive stress effectively enhances the matrix strength and plastic matching. Quenching refines grains and optimizes grain boundary structure to improve stress distribution capabilities and solve the problem of insufficient performance balance in the prior art. The present invention provides a reliable solution in the field of high-strength fasteners, which is particularly suitable for complex service environments such as aerospace and automobile manufacturing, promotes technological progress in the industry and significantly enhances application reliability and service life.
[0036] 3. The present invention achieves significant improvements in dimensional accuracy, mechanical properties and corrosion resistance of wire thread inserts through the coordinated optimization of precision cold forming process and surface treatment. Compared with the prior art, its pitch and thread outer diameter accuracy are higher, its strength and fatigue resistance are better, and corrosion and wear problems are effectively reduced. The cutting, cold forming and surface treatment steps complement each other. The precise design of dimensional control, dislocation strengthening and protective coating ensures the high stability and long life of the thread insert. Its innovative process provides a reliable solution for the high-performance fastener industry, meeting the stringent requirements of complex working conditions in fields such as aerospace and automotive manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The backscattering result of the round steel wire prepared in Example 1 of the present invention shows a stable {111} texture feature.
[0038] Figure 2 This is a transmission electron microscope morphology image of the twinned round steel wire prepared in Example 1 of the present invention.
[0039] Figure 3 These are the high-angle grain boundaries and low-angle grain boundaries of the round steel wire prepared in Example 1 of the present invention.
[0040] Figure 4 This is the interface between the Ni(Ti,Al) precipitate phase and α-Fe of the round steel wire prepared in Example 1 of the present invention.
[0041] Figure 5 This is the phase distribution of the short rod-shaped Ni(Ti,Al) precipitate prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0043] Example 1
[0044] A round steel wire for a steel thread insert of the present embodiment, the chemical components of the round steel wire include, by weight percentage: 0.10% C, 10.0% Cr, 0.50% Si, 0.30% Mn, 0.15% Ni, 0.01% Mo, 0.15% Cu, 0.005% Ti, 0.001% S, 0.025% P, 0.001% Al, 0.085% V, 0.008% Co, 0.008% Nb, and the balance is Fe and unavoidable impurities;
[0045] The round steel wire for steel thread inserts contains deformation twins with an average width of 30nm and an average density of 1.1×1012cm-2; the round steel wire for steel thread inserts contains short rod-shaped Ni(Ti,Al) precipitates with an average width of 5.0nm and an average length of 50nm. The short rod-shaped Ni(Ti,Al) precipitates in the round steel wire for steel thread inserts are dispersed inside the matrix grains with a spacing of 20nm. The interface between the Ni(Ti,Al) precipitates and the α-Fe in the matrix is a semi-coherent interface; the interface mismatch is 1.5%. The dislocation density of the round steel wire for steel thread inserts is 5.0×1014m-2. The matrix grains of the round steel wire for steel thread inserts are refined to an average grain size of 1.5μm after redistribution treatment, and the grains show {111} texture characteristics. In the round steel wire for wire thread inserts, the residual compressive stress distribution range at the interface between the Ni(Ti,Al) precipitate phase and the α-Fe matrix is 400MPa. The ratio of large-angle grain boundaries to small-angle grain boundaries in the round steel wire for wire thread inserts is 55:45.
[0046] A quenching process for round steel wire for a wire thread insert comprises the following steps:
[0047] S1: pre-treating the hot-rolled round steel wire rod for wire thread inserts to remove surface impurities, the pre-treatment process method is: placing the hot-rolled round steel wire rod for wire thread inserts in a pickling tank, adding 10wt.% dilute nitric acid solution, keeping stirring for 5 minutes, pickling to remove surface oxide scale, after the pickling is completed, rinse the hot-rolled wire rod with deionized water for 3 times, and place the rinsed hot-rolled wire rod in a hot air drying oven at 70°C for 30 minutes.
[0048] S2: austenitizing the round steel wire obtained in step S1 to obtain an austenitic wire rod; the process method of austenitizing is: heating the hot-rolled wire rod in step S1 to 1100°C at a heating rate of 5°C / min in a heating furnace, keeping the temperature for 3.0 minutes, and completing the austenitizing treatment to obtain an austenitic wire rod.
[0049] S3: subjecting the austenite wire rod obtained in step S2 to a primary quenching treatment to obtain a martensitic wire rod; the process method for the primary quenching is: quenching the austenite wire rod in step S2 in an oil bath at 180° C. and keeping it in the oil bath for 60 seconds to obtain a martensitic wire rod.
[0050] S4: The martensitic wire rod obtained in step S3 is subjected to redistribution treatment and secondary quenching in sequence to obtain a finished round steel wire for wire screw inserts; the process method of the secondary quenching is: the martensitic wire rod in step S3 is placed in a 420°C salt bath molten salt, and kept warm for 30 minutes to complete the redistribution treatment. After the redistribution treatment is completed, it is then subjected to room temperature water quenching to obtain a finished round steel wire for wire screw inserts.
[0051] S5: The finished round steel wire for wire screw inserts of S4 is subjected to drawing processing to obtain the round steel wire for wire screw inserts. The drawing process is as follows: a lubricant is applied to the surface of the finished round steel wire for wire screw inserts, and then the finished round steel wire for wire screw inserts is subjected to 5 drawing passes, each drawing pass having a deformation amount of 5%, and finally the round steel wire for wire screw inserts is obtained.
[0052] pass Figures 1 to 5 The results show that the round steel wire prepared in Example 1 of the present invention has remarkable excellence in microstructure and texture characteristics. Figure 1 The medium backscattering results show a stable {111} texture feature, which indicates that the material has achieved an ideal crystal orientation through process optimization during the preparation process, thus helping to improve the mechanical properties and fatigue performance of the material. Figure 2 The twin transmission electron microscope morphology in the figure further shows that there are a large number of twin structures in the round steel wire, which can effectively improve the strength and plasticity of the material, while helping to hinder the expansion of cracks and enhance the comprehensive mechanical properties of the material. Figure 3 The distribution of large-angle grain boundaries and small-angle grain boundaries displayed shows that the grain boundary structure in the material is obviously optimized. The existence of large-angle grain boundaries helps to improve the strength and toughness of the material, while small-angle grain boundaries can provide better dislocation strengthening effect. Figure 4 The interface structure between the Ni(Ti,Al) precipitate phase and the α-Fe matrix phase was revealed. The stability of this interface bonding plays an important role in the precipitation strengthening effect of the material, thereby significantly improving the fatigue resistance of the material. Figure 5 The distribution of short rod-shaped Ni (Ti, Al) precipitate phase is shown, and its uniform and fine distribution characteristics further prove the effectiveness of the precipitation phase control in the process, and this distribution can significantly improve the hardness and wear resistance of the material. In summary, the above graphical results fully prove that Example 1 of the present invention significantly improves the microstructure characteristics and performance of round steel wire by optimizing the process conditions, providing strong support for the engineering application of high strength, high fatigue life and high wear resistance.
[0053] Example 2
[0054] The present embodiment provides a round steel wire for a steel thread insert, wherein the chemical components of the round steel wire include, by weight percentage: 0.13% C, 10.9% Cr, 0.53% Si, 0.32% Mn, 0.18% Ni, 0.01% Mo, 0.16% Cu, 0.006% Ti, 0.001% S, 0.028% P, 0.001% Al, 0.087% V, 0.009% Co, 0.009% Nb, and the balance is Fe and unavoidable impurities;
[0055] The round steel wire for steel thread inserts contains deformation twins with an average width of 40nm and an average density of 1.7×1012cm-2; the round steel wire for steel thread inserts contains short rod-shaped Ni(Ti,Al) precipitates with an average width of 8.0nm and an average length of 80nm. The short rod-shaped Ni(Ti,Al) precipitates in the round steel wire for steel thread inserts are dispersed inside the matrix grains with a spacing of 26nm. The interface between the Ni(Ti,Al) precipitates and the α-Fe in the matrix is a semi-coherent interface; the interface mismatch is 1.8%. The dislocation density of the round steel wire for steel thread inserts is 6.5×1014m-2. The matrix grains of the round steel wire for steel thread inserts are refined to an average grain size of 1.8μm after redistribution treatment, and the grains show {111} texture characteristics. In the round steel wire for wire thread inserts, the residual compressive stress distribution range at the interface between the Ni(Ti,Al) precipitate phase and the α-Fe matrix is 360MPa. The ratio of large-angle grain boundaries to small-angle grain boundaries in the round steel wire for wire thread inserts is 58:42.
[0056] A quenching process for round steel wire for a wire thread insert comprises the following steps:
[0057] S1: pre-treating the hot-rolled round steel wire rod for wire thread inserts to remove surface impurities, the pre-treatment process method is: placing the hot-rolled round steel wire rod for wire thread inserts in a pickling tank, adding 10wt.% dilute nitric acid solution, keeping stirring for 6 minutes, pickling to remove surface oxide scale, after the pickling is completed, rinse the hot-rolled wire rod with deionized water for 3 times, and place the rinsed hot-rolled wire rod in a hot air drying oven at 73°C for 39 minutes.
[0058] S2: austenitizing the round steel wire obtained in step S1 to obtain an austenitic wire rod; the process method of austenitizing is: heating the hot-rolled wire rod in step S1 to 1115°C at a heating rate of 6°C / min in a heating furnace, keeping the temperature for 4.0 minutes, and completing the austenitizing treatment to obtain an austenitic wire rod.
[0059] S3: subjecting the austenite wire rod obtained in step S2 to a primary quenching treatment to obtain a martensitic wire rod; the process method for the primary quenching is: quenching the austenite wire rod in step S2 in an oil bath at 186° C. and keeping it in the oil bath for 62 seconds to obtain a martensitic wire rod.
[0060] S4: The martensitic wire rod obtained in step S3 is subjected to redistribution treatment and secondary quenching in sequence to obtain a finished round steel wire for wire thread inserts; the process method of the secondary quenching is: the martensitic wire rod of step S3 is placed in a salt bath molten salt at 426°C, and kept warm for 39 minutes to complete the redistribution treatment. After the redistribution treatment is completed, it is then subjected to room temperature water quenching to obtain a finished round steel wire for wire thread inserts.
[0061] S5: The finished round steel wire for wire screw inserts of S4 is subjected to drawing processing to obtain the round steel wire for wire screw inserts. The drawing process is as follows: a lubricant is applied to the surface of the finished round steel wire for wire screw inserts, and then the finished round steel wire for wire screw inserts is subjected to 4 drawing passes, each drawing pass having a deformation amount of 8%, and finally the round steel wire for wire screw inserts is obtained.
[0062] Example 3
[0063] A round steel wire for a steel thread insert of the present embodiment, the chemical components of the round steel wire include, by weight percentage: 0.16% C, 11.1% Cr, 0.56% Si, 0.33% Mn, 0.21% Ni, 0.02% Mo, 0.18% Cu, 0.006% Ti, 0.001% S, 0.031% P, 0.001% Al, 0.088% V, 0.010% Co, 0.010% Nb, and the balance is Fe and unavoidable impurities;
[0064] The round steel wire for steel thread inserts contains deformation twins with an average width of 51nm and an average density of 2.6×1012cm-2; the round steel wire for steel thread inserts contains short rod-shaped Ni(Ti,Al) precipitates with an average width of 11nm and an average length of 113nm. The short rod-shaped Ni(Ti,Al) precipitates in the round steel wire for steel thread inserts are dispersed inside the matrix grains with a spacing of 38nm. The interface between the Ni(Ti,Al) precipitates and the α-Fe in the matrix is a semi-coherent interface; the interface mismatch is 2.4%. The dislocation density of the round steel wire for steel thread inserts is 8.0×1014m-2. The matrix grains of the round steel wire for steel thread inserts are refined to an average grain size of 2.4μm after redistribution treatment, and the grains show {111} texture characteristics. In the round steel wire for wire thread inserts, the residual compressive stress distribution range at the interface between the Ni(Ti,Al) precipitate phase and the α-Fe matrix is 280MPa. The ratio of large-angle grain boundaries to small-angle grain boundaries in the round steel wire for wire thread inserts is 64:36.
[0065] A quenching process for round steel wire for a wire thread insert comprises the following steps:
[0066] S1: pre-treating the hot-rolled round steel wire rod for wire thread inserts to remove surface impurities, the pre-treatment process method is: placing the hot-rolled round steel wire rod for wire thread inserts in a pickling tank, adding 10wt.% dilute nitric acid solution, keeping stirring for 8 minutes, pickling to remove surface oxide scale, after the pickling is completed, rinse the hot-rolled wire rod with deionized water for 3 times, and place the rinsed hot-rolled wire rod in a hot air drying oven at 76°C for 45 minutes.
[0067] S2: austenitizing the round steel wire obtained in step S1 to obtain an austenitic wire rod; the process method of austenitizing is: heating the hot-rolled wire rod in step S1 to 1130°C at a heating rate of 8°C / min in a heating furnace, keeping the temperature for 4.2 minutes, and completing the austenitizing treatment to obtain an austenitic wire rod.
[0068] S3: The austenite wire rod obtained in step S2 is subjected to primary quenching treatment to obtain a martensitic wire rod; the process method of the primary quenching is: quench the austenite wire rod in step S2 in an oil bath at 192°C and keep it in the oil bath for 66 seconds to obtain a martensitic wire rod.
[0069] S4: The martensitic wire rod obtained in step S3 is subjected to redistribution treatment and secondary quenching in sequence to obtain a finished round steel wire for wire thread inserts; the process method of the secondary quenching is: the martensitic wire rod in step S3 is placed in a salt bath molten salt at 438°C, and the redistribution treatment is completed by keeping the temperature for 48 minutes. After the redistribution treatment is completed, the round steel wire for wire thread inserts is then subjected to room temperature water quenching to obtain a finished round steel wire for wire thread inserts.
[0070] S5: The finished round steel wire for wire screw inserts of S4 is subjected to drawing processing to obtain the round steel wire for wire screw inserts. The drawing process is as follows: a lubricant is applied to the surface of the finished round steel wire for wire screw inserts, and then the finished round steel wire for wire screw inserts is subjected to 4 drawing passes, each drawing pass having a deformation amount of 8%, and finally the round steel wire for wire screw inserts is obtained.
[0071] Example 4
[0072] A round steel wire for a steel thread insert of the present embodiment, the chemical components of the round steel wire include, by weight percentage: 0.22% C, 13.5% Cr, 0.60% Si, 0.35% Mn, 0.25% Ni, 0.03% Mo, 0.20% Cu, 0.007% Ti, 0.002% S, 0.035% P, 0.002% Al, 0.090% V, 0.012% Co, 0.012% Nb, and the balance is Fe and unavoidable impurities;
[0073] The round steel wire for steel thread inserts contains deformation twins with an average width of 65nm and an average density of 3.5×1012cm-2; the round steel wire for steel thread inserts contains short rod-shaped Ni(Ti,Al) precipitates with an average width of 15nm and an average length of 145nm. The short rod-shaped Ni(Ti,Al) precipitates in the round steel wire for steel thread inserts are dispersed inside the matrix grains with a spacing of 50nm. The interface between the Ni(Ti,Al) precipitates and the α-Fe in the matrix is a semi-coherent interface; the interface mismatch is 3.0%. The dislocation density of the round steel wire for steel thread inserts is 1.0×1015m-2. The matrix grains of the round steel wire for steel thread inserts are refined to an average grain size of 3.0μm after redistribution treatment, and the grains show {111} texture characteristics. In the round steel wire for wire thread inserts, the residual compressive stress distribution range at the interface between the Ni(Ti,Al) precipitate phase and the α-Fe matrix is 200MPa. The ratio of large-angle grain boundary to small-angle grain boundary in the round steel wire for wire thread inserts is 70:30.
[0074] A quenching process for round steel wire for a wire thread insert comprises the following steps:
[0075] S1: pre-treating the hot-rolled round steel wire rod for wire thread inserts to remove surface impurities, the pre-treatment process method is: placing the hot-rolled round steel wire rod for wire thread inserts in a pickling tank, adding 10wt.% dilute nitric acid solution, keeping stirring for 10 minutes, pickling to remove surface oxide scale, after the pickling is completed, rinse the hot-rolled wire rod with deionized water for 3 times, and place the rinsed hot-rolled wire rod in a hot air drying oven at 80°C for 60 minutes.
[0076] S2: austenitizing the round steel wire obtained in step S1 to obtain an austenitic wire rod; the process method of austenitizing is: heating the hot-rolled wire rod in step S1 to 1150°C at a heating rate of 10°C / min in a heating furnace, keeping the temperature for 5.0 minutes, and completing the austenitizing treatment to obtain an austenitic wire rod.
[0077] S3: subjecting the austenite wire rod obtained in step S2 to a primary quenching treatment to obtain a martensitic wire rod; the process method for the primary quenching is: quenching the austenite wire rod in step S2 in an oil bath at 200° C. and keeping it in the oil bath for 70 seconds to obtain a martensitic wire rod.
[0078] S4: The martensitic wire rod obtained in step S3 is subjected to redistribution treatment and secondary quenching in sequence to obtain a finished round steel wire for wire screw inserts; the process method of the secondary quenching is: the martensitic wire rod of step S3 is placed in a salt bath molten salt at 450°C, and the redistribution treatment is completed for 60 minutes. After the redistribution treatment is completed, room temperature water quenching is then performed to obtain a finished round steel wire for wire screw inserts.
[0079] S5: The finished round steel wire for wire screw inserts of S4 is subjected to drawing processing to obtain the round steel wire for wire screw inserts. The drawing process is as follows: a lubricant is applied to the surface of the finished round steel wire for wire screw inserts, and then the finished round steel wire for wire screw inserts is subjected to three drawing passes, each drawing pass having a deformation amount of 10%, and finally the round steel wire for wire screw inserts is obtained.
[0080] Comparative Example 1
[0081] It is basically the same as Example 1, except that in the S2 austenitizing treatment, the austenitizing temperature is reduced to 1050°C, which is lower than the minimum range (1100°C).
[0082] Comparative Example 2
[0083] It is basically the same as Example 1, except that in the S3 primary quenching process, the oil bath temperature is increased to 220°C, which is higher than the maximum range (200°C).
[0084] Comparative Example 3
[0085] It is basically the same as Example 1, except that in the S4 secondary quenching process, the salt bath molten salt temperature is set to 400°C, which is lower than the minimum range (420°C).
[0086] Comparative Example 4
[0087] It is basically the same as Example 1, except that in the S5 drawing process, the drawing deformation amount per pass is increased to 15%, which is higher than the maximum range (10%).
[0088] Comparative Example 5
[0089] It is basically the same as Example 1, except that in the S3 primary quenching process, the holding time is increased to 100 seconds, which is higher than the maximum range (70 seconds).
[0090] Comparative Example 6
[0091] It is basically the same as Example 1, except that in the S5 drawing process, the number of drawing passes is reduced to 2 times, which is lower than the minimum range (3 times).
[0092] Comparative Example 7
[0093] It is basically the same as Example 1, except that in the S4 redistribution process, the insulation time is shortened to 20 minutes, which is lower than the minimum range (30 minutes).
[0094] Comparative Example 8
[0095] It is basically the same as Example 1, except that in the S2 austenitizing treatment, the heating rate is increased to 15°C / min, which is higher than the maximum range (10°C / min).
[0096] Performance Testing:
[0097] The test method for the tensile strength of round steel wire is as follows: First, select a round steel wire sample that meets the standard requirements and ensure that there are no obvious defects on its surface. The diameter and length of the sample must meet the requirements of the test equipment. Then, fix the sample in the fixture of the tensile testing machine, ensure that the fixture is clamped and the sample remains vertical to prevent the sample from slipping or uneven force during the test. Start the tensile testing machine and perform axial tensile loading on the sample at a specified loading speed (usually 1 to 5 mm / min). During the tensile process, the test machine will record the load and the elongation of the sample in real time. When the sample breaks, record the maximum load value. At this time, the ratio of the load value to the initial cross-sectional area of the sample is the tensile strength of the sample. Finally, calculate the tensile strength according to the formula σ=Fmax / A, where σ is the tensile strength, Fmax is the maximum load before the sample breaks, and A is the initial cross-sectional area of the sample. At the same time, the test results are repeated for multiple times to verify the reliability of the data, and the data are sorted and analyzed according to relevant standards to obtain the final tensile strength value.
[0098] Fatigue strength: The test method for the fatigue strength of round steel wire is as follows: First, select a round steel wire sample that meets the test standard requirements, the length is usually 200mm, ensure that the surface of the sample is smooth and has no obvious defects, and the size and shape meet the requirements of the fatigue test equipment; then, install the sample on the fatigue testing machine, fix the two ends of the sample in the fixture, and the fixture must ensure that the coaxiality deviation is less than 1% to avoid eccentricity or uneven force during the test; start the fatigue testing machine, select the loading form as pull-pull loading according to the test requirements, set the loading frequency to 50Hz, and set the initial load range (the maximum stress is 50% to 70% of the material yield strength); during the test, the sample is alternating The specimen is repeatedly loaded under load, and the testing machine records the stress level and number of cycles in real time until the specimen breaks or reaches the set upper limit of the number of cycles (usually 10 times); if the specimen does not break, the stress amplitude is gradually increased (usually in increments of 5 MPa), and the test is repeated until the maximum bearing stress amplitude of the specimen is determined; the SN curve (stress-life curve) is drawn based on the test results, and the fatigue strength is the maximum stress under the corresponding set cycle life (10 times); finally, the test results are repeated at least 3 times to ensure the accuracy and reliability of the data, and the results are analyzed and reported in accordance with relevant standards, and the influence of environmental parameters on the test results is recorded.
[0099] Wear resistance test: The test method for round steel wire wear resistance is as follows: First, select a round steel wire sample that meets the test standard requirements, the length is usually 100mm~200mm, ensure that the sample surface is smooth and has no obvious defects, and remove surface oil and impurities; then, install the sample on the wear resistance testing machine, the fixture of the testing machine must ensure that the sample is firmly fixed and kept straight to avoid slipping or bending deformation during the test; select the friction working condition according to the test requirements, linear friction, set the loading pressure of the testing machine to usually 5N, the sliding speed to 100mm / s, and the wear stroke to 50mm, and select a suitable friction dual material (such as hard steel plate or ceramic material), the hardness of which is usually 60HRC, and ensure that the surface roughness of the dual material The roughness is Ra0.2μm; during the test, parameters such as loading force, friction force and sliding distance are recorded. The sample slides back and forth on the friction dual material. The test time is usually 30 minutes, or the sliding distance reaches 100m; after the test, the sample is removed and the mass of the sample before and after the test is measured using a precision balance with an accuracy of 0.1mg. The wear amount is calculated by the mass loss. At the same time, a three-dimensional optical profilometer or scanning electron microscope (SEM) is used to observe the surface wear morphology of the sample and the dual material, and the depth and width of the wear mark are measured; finally, the test results are subjected to at least 3 repeatability tests to ensure the accuracy and reliability of the data, and the wear resistance is analyzed according to relevant standards, while the influence of the test environment parameters is recorded.
[0100] The properties of the round steel wires of Examples 1 to 4 and Comparative Examples 1 to 8 are summarized in Table 2.
[0101] Table 1 Performance of round steel wires of Examples 1 to 4 and Comparative Examples 1 to 8
[0102]
[0103]
[0104] The main difference between Comparative Example 1 and Example 1 is that the austenitizing temperature is lower (1050°C), resulting in grain coarsening. As can be seen from Table 1, the tensile strength and fatigue strength of Comparative Example 1 are significantly lower than those of Example 1, while the wear resistance is slightly improved. The lower austenitizing temperature is not enough to form uniform and fine austenite grains, and the martensite structure generated after quenching is not fine enough, which weakens the strength and toughness of the material. However, larger grains and softer structures can slow down the wear process, so the wear resistance of Comparative Example 1 is slightly improved.
[0105] The main difference between Comparative Example 2 and Example 1 is that the initial quenching temperature is too high (220°C), resulting in insufficient martensite structure. As can be seen from Table 2, the tensile strength and fatigue strength of Comparative Example 2 are lower than those of Example 1, while the wear resistance is slightly improved. If the initial quenching temperature is too high, part of the austenite structure will not be fully transformed into high-hardness martensite, resulting in a decrease in the strength of the material. However, this incomplete quenching may form a softer structure, reducing the damage to the surface caused by wear, thereby slightly improving the wear resistance.
[0106] The main difference between Comparative Example 3 and Example 1 is that the secondary quenching temperature is lower (400°C), resulting in insufficient formation of the precipitation phase. As can be seen from Table 2, the tensile strength and fatigue strength of Comparative Example 3 are lower than those of Example 1, while the wear resistance is improved. The lower secondary quenching temperature will lead to insufficient precipitation strengthening phase, thereby weakening the strength and fatigue performance of the material. However, the softer structure has better adaptability to friction, which slightly improves the wear resistance of Comparative Example 3.
[0107] The main difference between Comparative Example 4 and Example 1 is that the drawing deformation is too large (15%), resulting in too high dislocation density. As can be seen from Table 2, the tensile strength and fatigue strength of Comparative Example 4 are lower than those of Example 1, while the wear resistance is improved. Excessive drawing deformation will lead to dislocation accumulation and stress concentration inside the lattice, making the material more brittle, and reducing strength and fatigue performance. However, due to the enhanced surface hardening effect, the wear resistance of the material is improved to a certain extent.
[0108] The main difference between Comparative Example 5 and Example 1 is that the initial quenching time is too long (100 seconds), resulting in excessive transformation of the martensite structure. As can be seen from Table 2, the tensile strength and fatigue strength of Comparative Example 5 are lower than those of Example 1, while the wear resistance is slightly reduced. Too long quenching time will cause coarsening of the internal structure, reduce the toughness of the material, and weaken the surface hardness, thereby reducing the wear resistance.
[0109] The main difference between Comparative Example 6 and Example 1 is that the number of drawing passes is insufficient (2 times), resulting in insufficient work hardening effect. As can be seen from Table 2, the tensile strength and fatigue strength of Comparative Example 6 are significantly lower than those of Example 1, while the wear resistance is slightly improved. Insufficient drawing passes will reduce the dislocation density of the material, resulting in a significant decrease in strength and fatigue properties. However, due to insufficient work hardening, the material surface is softer, which is helpful for friction adaptability to a certain extent, so that the wear resistance is improved.
[0110] The main difference between Comparative Example 7 and Example 1 is that the redistribution holding time is insufficient (20 minutes), resulting in insufficient formation of the precipitated phase. As can be seen from Table 2, the tensile strength and fatigue strength of Comparative Example 7 are lower than those of Example 1, while the wear resistance is slightly improved. Shorter holding time will lead to insufficient precipitation strengthening phase, and the strength and fatigue performance of the material are therefore weakened. However, the softer structure can provide better adaptability in friction, thereby slightly improving the wear resistance.
[0111] The main difference between Comparative Example 8 and Example 1 is that the heating rate is too high (15°C / min), resulting in grain coarsening and poor structural uniformity. As can be seen from Table 2, the tensile strength and fatigue strength of Comparative Example 8 are lower than those of Example 1, while the wear resistance is slightly improved. A higher heating rate will cause the grains to grow rapidly, thereby weakening the strength and toughness of the material. However, the coarsened structure can slow down the wear effect to a certain extent, so the wear resistance is slightly improved.
[0112] In summary, through the performance comparison analysis of Examples 1 to 4 and Comparative Examples 1 to 8, it can be seen that the embodiments show relatively excellent comprehensive performance in terms of tensile strength, fatigue strength and wear resistance, while the comparative examples have different degrees of performance decline due to the deviation of process parameters. Specifically, the embodiment optimizes the process parameters such as austenitizing temperature, quenching temperature and time, and drawing deformation, so that the grain refinement effect is significant, the precipitation strengthening phase is fully formed, and the strength and toughness of the material are fully exerted, showing a high level in the industry. However, due to reasons such as grain coarsening, insufficient precipitation phase, excessive residual austenite or stress concentration, the strength and fatigue properties of the comparative examples generally decrease, making it difficult to meet the requirements of high-end engineering applications. In terms of wear resistance, the embodiments show stable and excellent performance, the wear amount is lower than the industry average, and is suitable for high wear conditions. However, due to the softer organization or surface hardening effect, the wear resistance of some comparative examples (such as Comparative Example 3 and Comparative Example 6) is slightly improved, but the overall fluctuation is large and the stability is poor, and it is difficult to reach the performance level of the embodiments. The performance decline of the comparative example is mainly due to the deviation of the key process parameters from the optimal range. For example, too low austenitizing temperature (Comparative Example 1) leads to grain coarsening, abnormal quenching temperature or time (Comparative Example 2, Comparative Example 5) affects martensitic transformation and organizational uniformity, insufficient or excessive drawing process (Comparative Example 4, Comparative Example 6) leads to abnormal dislocation density or insufficient hardening effect, and unreasonable heating rate and holding time (Comparative Example 7, Comparative Example 8) affect precipitation phase formation and organizational uniformity. On the whole, the optimized process parameters of the embodiment can significantly improve the material properties, so that it can achieve a balance in tensile strength, fatigue strength and wear resistance, showing comprehensive advantages, while the comparative example shows a downward trend in performance, especially in terms of strength and fatigue performance, which is significantly lower than the embodiment. The main reason is that the deviation of the process parameters leads to grain coarsening or uneven organization. In general, the optimized process of the embodiment significantly improves the comprehensive performance of the round steel wire, meets the strict requirements of high-end applications for strength, fatigue life and wear resistance, and the performance fluctuation of the comparative example further verifies the important influence of the process parameters on the material properties.
[0113] Example 5
[0114] A method for preparing a wire screw sleeve of the present embodiment is as follows:
[0115] A1. Cut the round steel wire into small segments of predetermined length according to the specifications of the wire thread insert, and the tolerance range of the cutting length is controlled to be ±0.05mm.
[0116] A2. The small steel wire segment obtained in step A1 is formed by a spiral forming device; the forming process adopts a cold forming process, the forming temperature is controlled within the room temperature range, the axial pressure during forming is controlled to be 100MPa, and the forming speed is controlled to be 20mm / s; the pitch tolerance of the formed steel wire thread sleeve is ±0.02mm, and the thread outer diameter tolerance is ±0.05mm.
[0117] A3. The wire screw insert formed in step A2 is subjected to surface treatment, and the surface treatment comprises the following steps: first, the surface of the wire screw insert is cleaned using an ultrasonic cleaning device to remove residues and oil stains; then, an anti-rust lubricant is evenly coated on the surface of the cleaned wire screw insert, and the thickness of the lubricant coating layer is controlled to be 5 μm; finally, the coated wire screw insert is placed in a hot air drying oven at 120°C for curing treatment, and the curing time is 30 minutes to form a uniform lubricating protective layer.
[0118] Example 6
[0119] A method for preparing a wire screw sleeve of the present embodiment is as follows:
[0120] A1. Cut the round steel wire into small segments of predetermined length according to the specifications of the wire thread insert, and the tolerance range of the cutting length is controlled to be ±0.05mm.
[0121] A2. The small steel wire segment obtained in step A1 is formed by a spiral forming device; the forming process adopts a cold forming process, the forming temperature is controlled within the range of room temperature to 15°C, the axial pressure during forming is controlled to be 130MPa, and the forming speed is controlled to be 26mm / s; the pitch tolerance of the formed steel wire thread sleeve is ±0.02mm, and the thread outer diameter tolerance is ±0.05mm.
[0122] A3. The wire screw insert formed in step A2 is subjected to surface treatment, and the surface treatment comprises the following steps: first, the surface of the wire screw insert is cleaned using an ultrasonic cleaning device to remove residues and oil stains; then, an anti-rust lubricant is evenly coated on the surface of the cleaned wire screw insert, and the thickness of the lubricant coating layer is controlled to be 7 μm; finally, the coated wire screw insert is placed in a hot air drying oven at 135°C for curing treatment, and the curing time is 39 minutes to form a uniform lubricating protective layer.
[0123] Example 7
[0124] A method for preparing a wire screw sleeve of the present embodiment is as follows:
[0125] A1. Cut the round steel wire into small segments of predetermined length according to the specifications of the wire thread insert, and the tolerance range of the cutting length is controlled to be ±0.05mm.
[0126] A2. The small steel wire segment obtained in step A1 is formed by a spiral forming device; the forming process adopts a cold forming process, the forming temperature is controlled within the range of room temperature to 40°C, the axial pressure during forming is controlled to be 220MPa, and the forming speed is controlled to be 38mm / s; the pitch tolerance of the formed steel wire thread sleeve is ±0.02mm, and the thread outer diameter tolerance is ±0.05mm.
[0127] A3. The wire screw insert formed in step A2 is subjected to surface treatment, and the surface treatment comprises the following steps: first, the surface of the wire screw insert is cleaned using an ultrasonic cleaning device to remove residues and oil stains; then, an anti-rust lubricant is uniformly coated on the surface of the cleaned wire screw insert, and the thickness of the lubricant coating layer is controlled to be 11 μm; finally, the coated wire screw insert is placed in a hot air drying oven at 140°C for curing treatment, and the curing time is 54 minutes to form a uniform lubricating protective layer.
[0128] Example 8
[0129] A method for preparing a wire screw sleeve of the present embodiment is as follows:
[0130] A1. Cut the round steel wire into small segments of predetermined length according to the specifications of the wire thread insert, and the tolerance range of the cutting length is controlled to be ±0.05mm.
[0131] A2. The small steel wire segment obtained in step A1 is formed by a spiral forming device; the forming process adopts a cold forming process, the forming temperature is controlled within the range of 50°C, the axial pressure during forming is controlled to be 300MPa, and the forming speed is controlled to be 50mm / s; the pitch tolerance of the formed steel wire thread sleeve is ±0.02mm, and the thread outer diameter tolerance is ±0.05mm.
[0132] A3. The wire screw insert formed in step A2 is subjected to surface treatment, and the surface treatment comprises the following steps: first, the surface of the wire screw insert is cleaned using an ultrasonic cleaning device to remove residues and oil stains; then, an anti-rust lubricant is evenly coated on the surface of the cleaned wire screw insert, and the thickness of the lubricant coating layer is controlled to be 13 μm; finally, the coated wire screw insert is placed in a hot air drying oven at 150°C for curing treatment, and the curing time is 60 minutes to form a uniform lubricating protective layer.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A round steel wire for a wire thread insert, characterized in that: The chemical components of the round steel wire include, by weight percentage, 0.10-0.22% C, 10.0-13.5% Cr, 0.50-0.60% Si, 0.30-0.35% Mn, 0.15-0.25% Ni, 0.01-0.03% Mo, 0.15-0.20% Cu, 0.005-0.007% Ti, 0.001-0.002% S, 0.025-0.035% P, 0.001-0.002% Al, 0.085-0.090% V, 0.008-0.012% Co, 0.008-0.012% Nb, and the balance is Fe and unavoidable impurities.
2. The round steel wire for wire thread insert according to claim 1, characterized in that: The round steel wire contains deformation twins with an average width of 30 to 65 nm and an average density of 1.1×1012 to 3.5×1012 cm-2; The round steel wire contains a short rod-shaped Ni3(Ti,Al) precipitate phase, the average width of the Ni3(Ti,Al) precipitate phase is 5.0-15nm, and the average length is 50-145nm; The short rod-shaped Ni(Ti, Al) precipitate phase is dispersedly distributed inside the matrix grains, and the spacing between them is 20-50 nm.
3. The round steel wire for wire thread insert according to claim 2, characterized in that: The dislocation density of the round steel wire is 5.0×1014 to 1.0×1015 m-2; The matrix grains of the round steel wire are refined to an average grain size of 1.5 to 3.0 μm after redistribution treatment, and the grains exhibit {111} texture characteristics; In the round steel wire, the residual compressive stress distribution range at the interface between the Ni(Ti,Al) precipitate phase and the α-Fe matrix is 200-400MPa; The ratio of large-angle grain boundaries to small-angle grain boundaries in the round steel wire is (55-70):(30-45); the interface between the Ni3(Ti,Al) precipitation phase and the α-Fe in the matrix is a semi-coherent interface; and the interface mismatch is 1.5%-3.0%.
4. A quenching process for round steel wire for wire thread inserts, characterized in that: The following steps are involved: S1: pre-treating the hot-rolled round steel wire rod to remove surface impurities; S2: austenitizing the round steel wire obtained in step S1 to obtain an austenitic wire rod; S3: performing a primary quenching treatment on the austenite wire rod to obtain a martensitic wire rod; S4: performing a redistribution treatment and a secondary quenching treatment on the martensitic wire rod in sequence to obtain a finished round steel wire for a wire thread sleeve; S5: Drawing the finished round steel wire for wire thread insert to obtain the round steel wire for wire thread insert; the round steel wire is any one of the round steel wire for wire thread insert described in claims 1-3.
5. The quenching process of round steel wire for wire thread inserts according to claim 4, characterized in that: The pretreatment process in step S1 is as follows: placing the hot-rolled wire rod of round steel wire in a pickling tank, adding a 10wt.% dilute nitric acid solution, and stirring for 5 to 10 minutes, pickling to remove the surface oxide scale, and after the pickling is completed, rinsing the hot-rolled wire rod with deionized water for 3 times, and placing the rinsed hot-rolled wire rod in a hot air drying oven at 70 to 80°C for 30 to 60 minutes.
6. The quenching process of round steel wire for wire thread inserts according to claim 5, characterized in that: The austenitizing process in step S2 is as follows: placing the pretreated hot-rolled wire rod into a heating furnace, heating to 1100-1150° C. at a heating rate of 5-10° C. / min, and keeping the temperature for 3.0-5.0 min to complete the austenitizing treatment and obtain the austenitic wire rod.
7. The quenching process of round steel wire for wire thread inserts according to claim 6, characterized in that: The process of the primary quenching in step S3 is: placing the austenite wire rod obtained in step S2 into an oil bath at 180-200° C. for quenching, and keeping it in the oil bath for 60-70 seconds to obtain the martensitic wire rod.
8. The quenching process of round steel wire for wire thread inserts according to claim 7, characterized in that: The secondary quenching process of S4 is as follows: placing the martensitic wire rod in a salt bath molten salt at 420-450° C., keeping the temperature for 30-60 minutes to complete the redistribution treatment, and then performing room temperature water quenching to obtain a finished round steel wire for a wire thread sleeve.
9. The quenching process of round steel wire for wire thread inserts according to claim 8, characterized in that: The drawing process in step S5 is as follows: a lubricant is applied to the surface of the finished round steel wire for the wire thread insert, and then the round steel wire for the wire thread insert is drawn for 3 to 5 times, with a deformation of 5 to 10% in each drawing process, to finally obtain the round steel wire for the wire thread insert.
10. A wire thread insert, characterized in that: The preparation method of the wire screw sleeve is: A1. Cut the round steel wire into small segments of predetermined length according to the specifications of the wire thread insert, and the tolerance range of the cutting length is controlled to be ±0.05mm; A2. The steel wire segment obtained in step S1 is formed by a spiral forming device; the forming process adopts a cold forming process, the forming temperature is controlled within the range of room temperature to 50°C, the axial pressure during forming is controlled to be 100-300MPa, and the forming speed is controlled to be 20-50mm / s; the pitch tolerance of the steel wire thread sleeve after forming is ±0.02mm, and the outer diameter tolerance of the thread is ±0.05mm; A3. The wire thread insert formed in step S2 is subjected to surface treatment, wherein the surface treatment comprises the following steps: First, use ultrasonic cleaning equipment to clean the surface of the wire thread sleeve to remove residues and oil stains; Subsequently, the surface of the cleaned wire screw sleeve is evenly coated with an anti-rust lubricant, and the thickness of the lubricant coating layer is controlled to be 5 to 13 μm; finally, the coated wire screw sleeve is placed in a hot air drying oven at 120 to 150° C. for curing, and the curing time is 30 to 60 minutes to form a uniform lubricating protective layer.
Citation Information
Patent Citations
Steel wire thread sleeve
CN201982456U
Hot-rolled 1300MPa-grade B-containing spring steel wire rod and production process thereof
CN118007026A
Low-cobalt ultrahigh-strength steel with high and low-temperature impact energy for ocean engineering and preparation method of low-cobalt ultrahigh-strength steel
CN118703895A
Steel wire for spring, spring and its production method
JP2002194496A
Steel, steel for die and die using the same
JP2009242820A